2020
DOI: 10.1002/ijgo.13143
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status and clinical and demographic conditions with the prevalence of preterm birth

Abstract: Objective: To examine the effects of socioeconomic and demographic conditions on the prevalence of preterm birth in a local community.Methods: Pregnant women (aged ≥16 years) willing to provide informed consent in one of the two languages of the community were recruited in South Africa between August 2007 and January 2015. Specifically designed case report forms collected information and measurements prospectively.Results: After reviewing the medical records of 5806 women, it was possible to identify those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
5
8
0
Order By: Relevance
“…In our study, mid-upper arm circumference was significantly smaller in the spontaneous preterm birth group. In a previous study, we found that a small mid-upper arm circumference was strongly associated with a higher risk of spontaneous preterm birth [41]. In addition, many other studies confirm that women who were underweight during pregnancy or had a small mid-upper arm circumference, had an increased risk of preterm birth [15,18,42, and 43], suggesting that maternal under nutrition contributes to preterm birth.…”
Section: Discussionmentioning
confidence: 69%
“…In our study, mid-upper arm circumference was significantly smaller in the spontaneous preterm birth group. In a previous study, we found that a small mid-upper arm circumference was strongly associated with a higher risk of spontaneous preterm birth [41]. In addition, many other studies confirm that women who were underweight during pregnancy or had a small mid-upper arm circumference, had an increased risk of preterm birth [15,18,42, and 43], suggesting that maternal under nutrition contributes to preterm birth.…”
Section: Discussionmentioning
confidence: 69%
“…Since we, and others, have shown that MUAC, maternal education and household income play important roles in newborn and 1-year outcomes, these were used as confounders. [35,36] Statistical analyses were performed using the Statistica data analysis software system, version 13 (TIBCO Software Inc., USA). Descriptive statistics were used to describe continuous variables, which were compared between groups with analysis of variance (ANOVA).…”
Section: Methodsmentioning
confidence: 99%
“…Since we, and others, have shown that MUAC, maternal education and household income play important roles in newborn and 1-year outcomes, these were used as confounders. [ 35 , 36 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations